MnxOy- based cathodes for oxygen reduction reaction catalysis in microbial fuel cells. (15th February 2019) - Chiodoni, A.; Salvador, G.P.; Massaglia, G.; Delmondo, L.; Muñoz-Tabares, J.A.; Sacco, A.; Garino, N.; Castellino, M.; Margaria, V.; Ahmed, D.; Pirri, C.F.; Quaglio, M.
Abstract: The need to reduce the costs of renewable energy sources such as (bio)electrochemical systems, has pushed the research towards alternative materials, especially for cathodes performing the oxygen reduction reaction, trying to maintain a catalytic efficiency close to that of platinum or platinum-based catalysts. In this work, at first, we present a manganese oxide-based catalyst in the form of xerogel, providing a complete description of the material. Later on, we present the comparison of two nanostructured manganese oxide-based catalysts, prepared from the same precursor, manganese acetate, but with different templating agents and with two different nanostructures: the xerogel previously discussed, and the nanofibers. With these two nanostructures, we prepared carbon-based electrodes, obtaining cathodes to be tested in microbial fuel cells. One of these cathodes performed very well and its performance was comparable to that of the reference which used Pt/C as catalyst. Highlights: Inexpensive and eco-friendly catalysts prepared into several nanostructures. Comparison between catalytic performance of Mnx Oy xerogels and nanofibers. Correlation of Mnx Oy performance with morphological/structural properties. Definition of the role of the crystal size with the catalyst's performance. Mnx Oy -based cathode performance comparable to Pt/C reference in microbial fuel cell.